2020
DOI: 10.3390/su12135336
|View full text |Cite
|
Sign up to set email alerts
|

Cardoon Meal (Cynara cardunculus var. altilis) as Alternative Protein Source during Finishing Period in Poultry Feeding

Abstract: The Food and Agriculture Organization’s previsions show that by 2050 the world’s population will reach 9.6 billion people, and the request for a high value protein source will increase as well. Poultry can guarantee high value protein for humans, even in the poorest regions of the world. Hence, efficient poultry production is needed, matching with sustainable development. The residual meal from cardoon seed oil (used for biodiesel and biodegradable bioplastic production) is suitable for animal feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…On the other hand, the inclusion of CM also did not affect meat chemical composition in poultry, as reported by Buccioni et al [29], where this feed component was tested on the finishing period of Kabir chickens for about 30 days. In this case, SM was partially (16%) or completely replaced with CM.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, the inclusion of CM also did not affect meat chemical composition in poultry, as reported by Buccioni et al [29], where this feed component was tested on the finishing period of Kabir chickens for about 30 days. In this case, SM was partially (16%) or completely replaced with CM.…”
Section: Discussionsupporting
confidence: 61%
“…Since the Mugellese breed did not undergo to a strong selective pressure, nowadays, the subjects show a wide range of phenotypic variability. Comparing the FCR for this breed with that of commercial hybrid broilers (which ranges from about 1.2–1.5; Benyi et al, 2015 ), it cannot compete with the latter, but considering the lower growth rate of commercial breeds (such as the Kabir chicken and of other unselected poultry species such as duck; Attia et al, 2013 ; Buccioni et al., 2020 ), the Mugellese chicken exhibited comparable performances.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the above, CAMC, CC, CM are characterised by an interesting nutritional profile and digestibility, although the high level of fibre suggests a greater use for ruminants. Nevertheless, Zumbo et al 28 and Buccioni et al 29 investigated their use in poultry and pig sector. As reported by the authors, although no difference in growth performance was found, the acid profile of meat and eggs was improved, suggesting a potential use in monogastric farming as an alternative to soy-protein.…”
Section: Discussionmentioning
confidence: 99%